Association of epidermal growth factor receptor gene polymorphisms with advanced endometriosis in a Korean population - Lee, Gyoung Hoon; Choi, Young Min; Kim, Jong Mee; Shin, Jae Jun; Kim, Jung Gu; Moon, Shin Yong (European journal of obstetrics & gynecology and reproductive biology, 2012)
To determine if specific single nucleotide polymorphisms (SNPs) in the Epidermal Growth Factor Receptor (EGFR) gene were meaningful markers for the risk of advanced stage endometriosis in a Korean population. Case–control study in a collective of 299 women with endometriosis and 285 controls. Three polymorphisms (151904 A>T [T628T] on exon 16 [rs 17337023], 162093 G>A [Q787Q] on exon 20 [rs 10251977], and 181946 C>T [D994D] on exon 25 [rs 2293347]) were assessed by a Minor Groove Binder (MGB) primer/probe Taqman assay. In-silico haplotypes were deduced using the Haploview (version 3.32) software package. There were no statistically significant differences in the genotype or haplotype frequencies of the three EGFR polymorphisms between subjects with endometriosis versus the control group. Even when the endometriosis cases were subdivided into stage III and IV based on the ASRM criteria, no statistically significant differences in genotype distribution or haplotype frequencies were observed between the three groups. Our results suggest that the 151904 A>T, 162093 G>A, and 181946 C>T polymorphisms in the EGFR gene are not associated with advanced stage endometriosis in a Korean population. Our results are in agreement with the results reported by Inagaki et al.